(untitled) (Research, Society and Development, 2023)
The objective of this study is to analyze how obstetric violence is evidenced and characterize it according to the literature worldwide. To create this project, we used the methodological strategy Revisão Integrativa da Literatura, 14 works were selected for the construction of this study. Of the studies that composed the results, 7.14% were published in North America (Cuba); 35.71% in South America (Brazil); 35.71% in Africa (Kenya, Ethiopia and Africa); 14.28% in Asia (China and India) and 7.14% in Europe (Spain). Obstetric violence is common in health institutions, and lack of information is an aggravating factor. The preparation of professionals is fundamental to face and prevent inhuman acts against women during childbirth, as well as the primary monitoring of pregnancy and education on the rights of pregnant women. The creation of legislation for the protection of women throughout the process of childbirth and punishment of those responsible is essential. However, future studies focusing on the effective confrontation of obstetric violence may contribute even more to this field of research. In addition, the vision of professionals from various areas of health under the various faces of the theme.